2021
DOI: 10.1002/ldr.4111
|View full text |Cite
|
Sign up to set email alerts
|

Plant community change mediated heterotrophic respiration increase explains soil organic carbon loss before moderate degradation of alpine meadow

Abstract: Alpine meadows on the Qinghai‐Tibet Plateau (QTP) store a huge amount of plant and soil carbon (C). The degradation of the alpine meadow has led to a significant loss of soil organic C (SOC), which endangers its weak C sink. The change in heterotrophic respiration was hypothesized as one of the primary biological processes for the SOC loss alongside the degradation of alpine meadow. However, little is known about how land degradation impacts Rh due to changes in plant communities and consequent labile organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…Previous studies have demonstrated that legume-based cropping minimized the Q 10 of SOC mineralization at 0-20 cm soil depth (Ghimire et al, 2019). Such a result might be attributed to the increased substrate availability under diversified cropping less sensitive to temperature changes requiring low activation energy (Qin et al, 2019;Lai et al, 2021). Despite a few studies on decreasing Q 10 of SOM mineralization by legume-based cropping (Ghimire et al, 2019) or by nature fallow (Zhang et al, 2022), large knowledge gaps remained on the fate and driving factors of SOM mineralization in response to increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that legume-based cropping minimized the Q 10 of SOC mineralization at 0-20 cm soil depth (Ghimire et al, 2019). Such a result might be attributed to the increased substrate availability under diversified cropping less sensitive to temperature changes requiring low activation energy (Qin et al, 2019;Lai et al, 2021). Despite a few studies on decreasing Q 10 of SOM mineralization by legume-based cropping (Ghimire et al, 2019) or by nature fallow (Zhang et al, 2022), large knowledge gaps remained on the fate and driving factors of SOM mineralization in response to increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, soil microorganisms (e.g., diazotrophs, phosphate‐solubilizing bacteria, arbuscular mycorrhizal fungi, etc.) may aid in the restoration of degraded grasslands by improving plant resistance to environmental stresses (Ezawa & Saito, 2018; Lai et al, 2021; Pii et al, 2015; Singh, 2015). On the other hand, soil microbes such as nitrifying/denitrifying bacteria and plant pathogens may enhance grassland degradation by intensifying soil nutrient loss or plant diseases (Che et al, 2017; Lennon & Houlton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…作用 (Coban et al, 2022;Liu et al, 2023)。研究证实草 地退化可以通过改变土壤养分和植物特征来驱动 土壤微生物多样性和功能的变化 (Luo et al, 2020)。 与未退化草地相比, 退化草地土壤细菌和真菌群落 多样性、组成、生物网络和功能基因存在显著差异 (Li et al, 2016;Luo et al, 2020。土壤微生物群 落在草地退化过程中可能具有双重作用 (Xun et al, 2018;Coban et al, 2022)。一方面, 土壤微生物(如固 氮菌、溶磷菌、丛枝菌根真菌等)可通过提高植物对 环境胁迫的抗性来促进退化草地的恢复 (Ezawa & Saito, 2018;Lai et al, 2021)。另一方面, 土壤传播的 病原体会严重威胁植物的健康, 加剧草地退化 (Che et al, 2019;Zhang Q et al, 2022)…”
unclassified